1994
DOI: 10.3109/00365549409008635
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Diarrhea due to Verotoxin-producing Escherichia coli in the Canadian Northwest Territories

Abstract: In the summer of 1991 a large outbreak of Escherichia coli O157:H7 associated diarrhea occurred in 6 Inuit communities in the Canadian Northwest Territories. The total population of these communities is 5,292. Of the 521 individuals who developed diarrhea, 152 (29%) were positive for E. coli O157:H7 on stool culture or positive by verotoxin analysis. Median age was 6 years. The attack rate for children < 1 year was 43% in the major affected community of Arviat. Hemolytic-uremic syndrome (HUS) developed in 22 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 23 publications
1
23
0
2
Order By: Relevance
“…The cold northern climate keeps persons indoors, which amplifi es the effects of household crowding, smoking, and inadequate ventilation. Crowded living conditions increase person-to-person spread of infectious diseases and favor the transmission of respiratory diseases (18)(19)(20), tuberculosis (12), gastrointestinal diseases (21), and skin infections (22). In many smaller isolated communities, inadequate sewage disposal systems and water supplies pose a substantial risk to health, resulting in periodic epidemics of diseases transmitted by the fecal-oral route (21,23).…”
Section: Inadequate Housing/crowded Living Conditionsmentioning
confidence: 99%
“…The cold northern climate keeps persons indoors, which amplifi es the effects of household crowding, smoking, and inadequate ventilation. Crowded living conditions increase person-to-person spread of infectious diseases and favor the transmission of respiratory diseases (18)(19)(20), tuberculosis (12), gastrointestinal diseases (21), and skin infections (22). In many smaller isolated communities, inadequate sewage disposal systems and water supplies pose a substantial risk to health, resulting in periodic epidemics of diseases transmitted by the fecal-oral route (21,23).…”
Section: Inadequate Housing/crowded Living Conditionsmentioning
confidence: 99%
“…In human infections, O157 and the other serotypes mentioned above may cause bloody diarrhea and, more precisely, may lead to hemolytic-uremic syndrome and to thrombotic and thrombocytopenic purpura in children and adults, respectively (33,57). Illness is often linked to the consumption of contaminated or undercooked ground beef (6,14,15,45,46,47,49,50,51,54). For instance, in Scotland 512 persons were infected by E. coli O157:H7 after consumption of beef, and 34 cases of hemolyticuremic syndrome and 17 deaths were reported (18).…”
mentioning
confidence: 99%
“…Of the 21 documents reviewed, eight (38%) reported trends between age and the occurrence of foodborne and waterborne illness (7,8,19,25,(28)(29)(30)(31). Of these, six (75%) noted higher prevalence in children up to 14 years old (7,19,(28)(29)(30)(31), One study did not report any difference due to age (8) and one showed that most of the trichinosis cases were in those over 60 years old and were more likely to be female (25).…”
Section: Demographic and Social Factorsmentioning
confidence: 99%
“…Of these, six (75%) noted higher prevalence in children up to 14 years old (7,19,(28)(29)(30)(31), One study did not report any difference due to age (8) and one showed that most of the trichinosis cases were in those over 60 years old and were more likely to be female (25). Of the six documents that reported some form of trend by male/female gender, half noted approximately equal distribution for botulism (16), E. coli (28) and hepatitis A (30,31). Overcrowding in homes was noted in four articles, particularly during winter (5,29,30,31).…”
Section: Demographic and Social Factorsmentioning
confidence: 99%